Does foreign direct investment in Ghana promote welfare? - Ferguson K. Gidiglo; Akua Agyeiwaa Afrane; Kofi A.A-O. Agyei-Henaku; Charlotte Badu-Prah; Francis Srofenyoh; Justice G. Djokoto (Social Sciences and Humanities Open, 2023)
Beyond the economic indicators of development is the welfare of citizens. This paper assessed the effect of foreign direct investment on welfare (human development) in Ghana. Unlike other studies on the subject that did not account for the unit interval property of the human development index (between 0 and 1 inclusive), we departed from existing studies on the welfare effects of foreign direct investment by accounting for the unit interval property (between 0 and 1, inclusive) of the human development index. Unlike country-specific studies on the subject that used time-series data with the associated time series modelling, we employed an unbalanced panel data of 41 countries in Africa over the period 1990 to 2019. We relied on the elasticities of the generalised estimation equations and isolated the effect of Ghana. Following the elasticities of the generalised estimation equations, the partial effect of foreign direct investment on welfare in Ghana was not statistically significant. The total effect of foreign direct investment on welfare in Ghana was also found to be statistically insignificant. Further, the total effect of foreign direct investment on welfare in other African countries was found to be statistically insignificant. Ghana and other African countries should re-assess their foreign direct investment policies vis-à-vis their effect on welfare. The interaction of policy could produce different results and can be researched subsequently.